Kajian Hukum atas Determinan Tindakan Asusila terhadap Anak di Bawah Umur dengan Retardasi Mental - Pakaya, Juwana; Puluhulawa, Moh. Rusdiyanto U; Puluhulawa, Irlan (Adagium: Jurnal Ilmiah Hukum, 2025)
The purpose of this study is to examine the factors that trigger immoral acts in minors with mental retardation in the jurisdiction of the Bone Bolango Police, as well as to evaluate the extent to which legal protection for victims has been effective. The approach applied in this study is empirical law with qualitative methods, where primary data was collected through interviews with investigators from the Women and Children Protection Unit (PPA), victims, and other related parties, accompanied by direct monitoring of the case handling process. Additional data sources were collected based on official archives, legal regulations, and scientific works. The findings of this study show that the dominant factors causing sexual abuse against children with mental retardation include the victims' limited cognitive and communication abilities, weak family supervision, low legal awareness in the community, and the influence of the environment and the development of information technology. The main challenges in implementing legal protection include limited police personnel, lack of supporting facilities, and social stigma against children with disabilities. The implications of this study emphasize the importance of strengthening an adaptive legal protection system, improving the competence of officials, providing safe shelters, and conducting continuous legal education for the community. This study recommends fostering collaboration between law enforcement agencies, families, and the community in preventive efforts and case handling, as well as promoting the formulation of policies that are more child-friendly toward children with mental disabilities as a preventive measure against sexual crimes.